The Shanghai Cooperation Organization versus the North Atlantic Treaty Organization: Security Dilemma of Growing Powers - KUZNETCOV, Vasilii M.; KUZNETSOVA, Ekaterina V. (Journal of Advanced Research in Law and Economics; Vol 7 No 2 (2016): JARLE, Volume VII, Issue 2(16), Spring 2016, 2016)
The goal of this research was to analyze the Shanghai Cooperation Organization in comparison to the North Atlantic Treaty Organization, as well as to analyze geopolitical implications of very existence of this particular model that contributes to a classic security dilemma. An interest in such research arose in reference to a continuing speculation over a true nature of the Shanghai Cooperation Organization. The Organization is often seen as an adversary to the North Atlantic Treaty Organization, as a part of an ongoing standoff between the West and the East. Among a great number of international organizations the Shanghai Cooperation Organization can undoubtedly claim the status of an important regional cooperation, especially when for the first time in more than ten years, the Organization is accepting new members. Analyzing the Organization, especially by doing so in comparison to North Atlantic Treaty Organization, allowed us to draw certain conclusions. Even though, the Shanghai Cooperation Organization is not a military alliance (especially having new members on board that have different political interests), the Organization will continue claiming the status of a regional dominant player, that aspires to bring back the influence over most of the North-Eastern Hemisphere. While the origin, goals, and structure of the Organization is very much different from the one of the North Atlantic Treaty Organization, it is expected that certain shifts will happen over the next decades. The main conclusion made from the research is that the very existence of the Shanghai Cooperation Organization, just like the existence of the North Atlantic Treaty Organization will keep developing a very deep and dangerous security dilemma that already exists.